Adhesive strength between an industrial render mortar with CDW aggregates and a ceramic substrate - Brazão Farinha Catarina; Silva André; Prigent William; Gomes Ricardo; Bastos David; Pederneiras Cinthia; Veiga Rosário (MATEC Web of Conferences)
The incorporation of construction and demolition wastes (CDW) as recycled aggregates (RA) in traditional mortars or concretes has been widely assessed in recent years. With this knowledge it is possible to move on to evaluate industrial products with these types of aggregates. In this research the composition of an industrial render mortar is modified to incorporate RA as aggregates. RA replaced part of the limestone aggregates originally used as natural aggregates. The replacement was by weight and the percentage ratio of 30 %, 50 % and 100 %. Three different CDWs were collected directly from recycling plants. Two of them were classified as mixed recycled aggregates and the other one as recycled concrete aggregate. This investigation is mainly focused on the influence of the RA incorporation in the mortars’ adhesive strength to a ceramic substrate, considering that the adhesive strength is an essential property for render mortars and directly determines their durability. The maximum feasible RA incorporation in each case, without affecting the mortar performance, was determined. The adhesive strength between the renders and the substrate was assessed according to EN 1015-12. It was concluded that until 30 % of replacement the adhesive strength is higher than 0.30 MPa for all mortars tested